The Research of Wire Rope Defect Using Contactless Dynamic Method - ŠUTINYS, Ernestas; Dzedzickis, Andrius; Bučinskas, Vytautas (Solid state phenomena, 2016)
This paper is intended to reveal possibilities of defects finding in the wire ropes using dynamic properties of the tensed wire rope using specially designed test rig. The subject of the research is the tensioned wire rope with broken wires, located on surface of the rope.Fragment of steel rope (4 mm diameter and 1.35 m length) was tested experimentally in order to find mentioned defects. A measurement of vibrations of the wire fragment on this test rig was performed using contactless vibration sensors. Fragment of the rope, installed in the test rig was excited with electrodynamics vibrator, which created sinusoidal excitement indirectly, i.e. through own frame. Research of vibrations of the rope was performed in wide ranges of frequencies and desired dynamic properties of the rope fragment as a dynamic system was obtained. Finally, results of the experimental research are presented and conclusions are drawn.